using the proof above (although Jeff is not 2000 years old):
-2√2 = -2 * (irrational number) = (rational number) * (irrational number) = irrational number.
Remember, however, (irrational number) * (irrational number) can produce (rational number) - e.g. → √2 * √2 = 2
Subhotosh Khan is quite right. My proof was incomplete. I shall go visit the corner where denis lives, but Subhotosh must go too because he forgot that there is one rational number that always gives a rational product when multiplied by an irrational number.
\(\displaystyle Assume\ u\ is\ an\ irrational\ number,\ a\ and\ b\ are\ non\text{-}zero\ integers,\ and\ u * \dfrac{a}{b}\ is\ rational \implies\)
\(\displaystyle there\ exist\ integers\ c\ and\ d\ such\ that\ u * \dfrac{a}{b} = \dfrac{c}{d} \implies u = \dfrac{bc}{ad},\ but\)
\(\displaystyle a,\ b,\ c,\ and\ d\ are\ integers \implies bc\ and\ ad\ are\ integers \implies\)
\(\displaystyle u\ is\ a\ rational\ number,\ which\ is\ a\ contradiction.\)
So an irrational number times a non-zero rational number is always irrational.
Come Subhotosh, we shall go to the corner together. I am so old that I need an arm to lean upon.
Edit: Halls of Ivy's proof is much more elegant them mine.